(untitled) (Nigerian Journal of Technology, 2016)
This paper presents the design of a technological framework for electronic voting (E-voting) systems in Nigeria. The traditional voting system with paper ballots used in the Nigeria electoral system is time consuming and in most cases marred with irregularities due to system and/or human errors. These irregularities usually results in inconclusive electoral decisions, violent arguments, and expensive litigations. Certain technologies and recently card readers with biometric authentication have been employed to achieve transparent polls. However, high level frauds still accompany results due to human control of these technological devices and have not generated the required trust resulting in a drastic decrease in voter participation. The framework presented here seeks to combine different e-voting technologies in a way that best suit the Nigeria electoral system in order to build trust and boost participation. The result is an automated polling system that requires minimum supervision with adequate transparency and accuracy of the voting process. The framework showcased how a cost saving real-time electoral procedure can be achieved, with the presentation of precise and accurate results at the end of any election. http://dx.doi.org/10.4314/njt.v35i3.22